Anaplasmosis in the Amazon: diagnostic challenges, persistence, and control of Anaplasma marginale and Anaplasma phagocytophilum - Mauri Pablo, Jhorsan David; Del Solar, Jakson Jacob Chuquimia; Hinojosa Enciso, Elthon Thomas; Polveiro, Richard Costa; Vieira, Dielson da Silva; Ramos Sanchez, Eduardo Milton; Bardales Escalante, William; Maicelo Quintana, Jorge Luis; Lopez Lapa, Rainer Marco (Frontiers in Veterinary Science, 2025)
Anaplasmosis remains a significant threat to livestock production in tropical regions, particularly in the Amazon basin, where ecological complexity and limited veterinary infrastructure challenge effective disease management. This review focuses on Anaplasma marginale and Anaplasma phagocytophilum, the primary species associated with bovine and granulocytic anaplasmosis, respectively. We examine the current state of diagnostic tools, highlighting the limited accessibility of molecular techniques in rural settings and the emerging but underutilized potential of technologies. Persistent infection and antigenic variation are explored as major obstacles for disease eradication and vaccine development. Although live attenuated and inactivated vaccines are in use for A. marginale, none provide sterilizing immunity, and no commercial vaccines exist for A. phagocytophilum. The review evaluates recent advances in recombinant antigens, chimeric constructs, and genetically attenuated strains, as well as future directions involving multiepitope design, novel adjuvants, and next-generation vaccine platforms. Additionally, we assess the role of tick control in disease prevention and emphasize the importance of integrated strategies in regions like the Amazon. Together, these findings underscore the need for context-specific solutions that address the ecological and epidemiological complexity of anaplasmosis in the Amazon basin.